2020
DOI: 10.1002/jbmr.4330
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Is Causally Associated With Reduced Serum Osteocalcin: A Genomewide Association and Mendelian Randomization Study

Abstract: Recent advances indicate that bone and energy metabolism are closely related. However, little direct evidence on causality has been provided in humans. We aimed to assess the association of three bone-related biomarkers-25 hydroxyvitamin D (25OHD), parathyroid hormone (PTH), and osteocalcin (OCN)-with several metabolic phenotypes and investigate any causal relevance to the associations using a Mendelian randomization (MR) study. Serum 25OHD, PTH, and total OCN were measured at baseline in 5169 eligible Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
0
24
0
1
Order By: Relevance
“…Besides, some studies have suggested that SMM, not BFM, is highly associated with BMD, 27–31 while others have shown that BFM, not SMM, is a key contributor to BMD. 32 , 33 Still, other studies have found that both BFM and SMM are significant indicators of BMD. 34–36 Studies of BFM and BMD in childhood have also presented mixed results, reporting positive, 37 , 38 negative, 39 or null associations.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, some studies have suggested that SMM, not BFM, is highly associated with BMD, 27–31 while others have shown that BFM, not SMM, is a key contributor to BMD. 32 , 33 Still, other studies have found that both BFM and SMM are significant indicators of BMD. 34–36 Studies of BFM and BMD in childhood have also presented mixed results, reporting positive, 37 , 38 negative, 39 or null associations.…”
Section: Discussionmentioning
confidence: 97%
“…We followed the method suggested by S.Burgess et al (URL: http://mendelianrandomization.com/) to calculate the power when genetically predicting binary exposure. 26,27 We calculated beta 2 ×2×MAF×(1-MAF), where MAF indicates minor allele frequency, of each genetic instruments and the sum of the values was the coefficient of determination of exposure. Despite the limitation, this approach of using odds ratios as a proxy for prevalence ratio was necessary as genetic beta effect sizes were not scaled to prevalence increase of a unit of an exposure in GWAS.…”
Section: Methodsmentioning
confidence: 99%
“…Post hoc power calculation for MR analysis was performed by an online tool (URL: https://sb452.shinyapps. io/power/), followed the method suggested by S. Burgess (URL: http://mendelianrandomization.com/) [33,34]. We calculated beta^2*2*MAF*(1-MAF), where MAF indicates minor allele frequency, of each instrumented SNP and summed the values for the coefficient necessary for the power calculator.…”
Section: Summary-level Mr Analysis Methodsmentioning
confidence: 99%